Dance Creativity in Kindergarten: Improvisation as a Method for Identifying Dance Talent in Children - Jurgec, Ana Tina (Selected Contemporary Research on Special Needs, Giftedness, and Talent in Slovenia, 2025)
Dance improvisation is a spontaneous and free form of expression that intertwines movement and imagination, creating space for creativity. The creativity expressed through dance improvisation represents a key category in identifying dance talent in children, as it provides insight into their ability for free expression and original movement. The aim of our study was to explore the characteristics of dance improvisation in early childhood, with a focus on physical activity and the formation of movement in children. We employed a quantitative research approach, collecting data through an observational protocol. The study included 246 children aged 5–6 years from 38 public kindergartens across Slovenia. Our findings serve as an important foundation for further research on monitoring dance improvisation in preschool children and for a deeper understanding of the role of body movement in children's creative dance expression.